RANCANG BANGUN SISTEM PELAPORAN PELANGGARAN PARKIR BERBASIS ANDROID - Dinda Prakoso, Irvan; Sudarma, Made; Arsa Suyadnya, I Made (Jurnal SPEKTRUM, 2019)
The high level of ownership of private vehicles will require large parking lots in certain zones. Not all places are able to provide sufficient parking space, so that the road body around it is used for parking lots. This will cause traffic problems. Utilization of technology can be one solution to overcome these problems. The purpose of this research is to design and build an Android-based parking violation reporting system so that the community can take part in reporting violations in the form of photos that are directly sent to the DLLAJ server (Road Transport Traffic Service) and make it easier for officers in their handling. System modeling plans include the Use Case Diagram, Activity Diagram and database structure. The process of this application is to send a parking violation photo to the server, then extract the photo to get the metadata (latitude and longitude) that shows the location of the violation. Based on the results of testing the application with the Black Box Testing method, the overall functionality of the application has been declared successful. In addition, based on the results of the System Usability Scale (SUS) test, a score of 79.5 means that the value is above the average and the application can be accepted by the user.